Psicologia da moralidade de psicanálise : um estudo sobre o sentimento de vergonha - Schimith, Polyana Barbosa (2013)
This thesis was aimed at investigating the feeling of shame and its relation to morality, proposed by Yves de La Taille (2002a), as well as the proposition of Jacques Lacan (1969-1970/1992), according to which this feeling is absent on contemporaneity. The research, of qualitative and exploratory nature, was an empirical study involving 15 male participants, aged between 25 and 30 years old and college graduates. We proceeded to collect and analyze the data according to the clinical method of Piaget (1932/1994, 1926/2005b). Individual semi-structured interviews were conducted, based on two fictional stories, as well as an interview on the concept of the feeling of shame. The first story features a situation of moral transgression and the second, an exposure situation. Data were categorized and then analyzed in the light of the theories of La Taille (2002a) and Lacan (1969-1970/1992). The results reveal that participants show the feeling of shame not at the immoral situation, but at the exposure situation. The notion of this feeling is linked primarily to exposure and judgment of the subject himself/herself and /or of others. The study aims to contribute to a greater understanding of the contribution of the feeling of shame in moral issues in the context of contemporary society, and indicate new directions for research on the topic. The theoretical reflections on the existing literature and on data obtained during collecting, led to updated theoretical propositions of Psychoanalysis to the scope of the Psychology of Morality. Those demand inevitable update on the thought about inherent intrapsychic factors in the genesis or development of morality.